2005
DOI: 10.2172/876525
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty analysis of steady state incident heat flux measurements in hydrocarbon fuel fires.

Abstract: The objective of this report is to develop uncertainty estimates for three heat flux measurement techniques used for the measurement of incident heat flux in a combined radiative and convective environment. This is related to the measurement of heat flux to objects placed inside hydrocarbon fuel (diesel, JP-8 jet fuel) fires, which is very difficult to make accurately (e.g., less than 10%). Three methods will be discussed: a Schmidt-Boelter heat flux gage; a calorimeter and inverse heat conduction method; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 4 publications
2
22
0
Order By: Relevance
“…Figueroa et al [2005] estimated the maximum uncertainty in heat flux using the inverse heat conduction program IHCP1D (Beck Engineering & Associates) to be about ±20% for a cylindrical calorimeter near, but not in, a fire. Nakos [2005] showed that the incident flux uncertainty could be as large as ±40% in situations broadly similar to those of the present experiments. An uncertainty of ±40% will be assumed for the present experiments both in Penlight and in FRH.…”
Section: Heat Flux Measurements Made By Beck Engineering Ihcp1dsupporting
confidence: 88%
See 4 more Smart Citations
“…Figueroa et al [2005] estimated the maximum uncertainty in heat flux using the inverse heat conduction program IHCP1D (Beck Engineering & Associates) to be about ±20% for a cylindrical calorimeter near, but not in, a fire. Nakos [2005] showed that the incident flux uncertainty could be as large as ±40% in situations broadly similar to those of the present experiments. An uncertainty of ±40% will be assumed for the present experiments both in Penlight and in FRH.…”
Section: Heat Flux Measurements Made By Beck Engineering Ihcp1dsupporting
confidence: 88%
“…In the absence of a known calibration constant for the convective heat flux of the gauges used in the present experiments, the calibration constant of the convective fraction will be assumed to have the same relationship to the radiative calibration constant as the gauge calibrated by Diller. The overall uncertainty for Schmidt-Boelter total heat flux gauges has been estimated to be ±23% for the net absorbed heat flux and ±39% for the incident heat flux under conditions similar to those of the present experiments [Nakos, 2005].…”
Section: Total Hfgsupporting
confidence: 70%
See 3 more Smart Citations